Peran Social Media Marketing Dalam Meningkatkan Purchase Intention Pada Frozen Food - Khoirur Riza, Muhamad; Renny Risqiani (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This study aims to determine the effect of the role of Social Media Marketing in increasing Purchase Intention on Frozen Food. Samples were taken with individual criteria, namely people who had purchased Frozen Food products online at Social Media Marketing in the past year. This study uses primary data obtained through questionnaires distributed to 100 respondents. Based on the time period, the data collected in this study is cross-sectional in nature. The analytical method used is the Structural Equation Model (SEM). The results of this study indicate that Social Media Marketing has a positive impact on Brand Awareness; Social Media Marketing has a positive impact on Brand Engagement; Social Media Marketing does not have a positive impact on Purchase Intention; Brand Awareness does not have a positive impact on Purchase Intention; Brand Awareness does not mediate relationship between Social Media Marketing and Purchase Intention; Brand Engagement does not have a positive effect on Purchase Intention; Brand Engagement mediates the relationship between Social Media Marketing and Purchase Intention